Singapore story memoirs of Lee Kuan Yew - Lee, Kuan Yew 1923-2015 (Marshall Cavendish Editions The Straits Times Press, 2015)
The Singapore Story is the first volume of the memoirs of Lee Kuan Yew, the man who planted the island state of Singapore firmly on the map of the world. It was first published in 1999. In intimate detail, Lee recounts the battles against colonialists, communists and communalists that led to Singapore's independence. With consummate political skill, he countered adversaries, sometimes enlisting their help, at others opposing them, in the single-minded pursuit of Singapore's interests. We read how he led striking unionists against the colonial government, how over tea and golf he fostered ties.